The Association between Glomerular Filtration Rate Estimated on Admission and Acute Stroke Outcome: The Shiga Stroke Registry - Nugroho, Aryandhito Widhi (J Atheroscler Thromb, 2018)
Aim: Although renal dysfunction has been identified as a novel risk factor affecting stroke prognosis, few have analyzed the association within large-scale population-based setting, using wide-range estimated glomerular filtration rate (eGFR) category. We aimed to determine the association of admission eGFR with acute stroke outcomes using data from a registry established in Shiga Prefecture, Japan. Methods: Following exclusion of patients younger than 18 years, with missing serum creatinine data, and with onset more than 7 days prior to admission, 2,813 acute stroke patients registered in the Shiga Stroke Registry year 2011 were included in the final analysis. The Japanese Society of Nephrology equation was used to estimate GFR. Multivariable logistic regression was performed to analyze the association of eGFR with all-cause in-hospital death (modified Rankin Scale [mRS] 6), and atdischarge death/disability (mRS 2–6). Separate analyses were conducted within stroke subtypes. Results: Compared to eGFR 60–89 mL/min/1.73 m(2), adjusted odds ratios (ORs) and 95% confidence interval [95% CI] for in-hospital death (in the order of eGFR < 45, 45–59, and ≥ 90 mL/min/1.73 m(2)) were 1.54 [1.04–2.27], 1.07 [0.72–1.58], and 1.04 [0.67–1.59]. Likewise, adjusted ORs [95% CI] for at-discharge death/disability were 1.54 [1.02–2.32], 0.97 [0.73–1.31], and 1.48 [1.06–2.05]. Similar pattern was further evident in the eGFR < 45 mL/min/1.73 m(2) group for both outcomes within acute ischemic stroke patients. Conclusions: Our study has ascertained that in acute stroke, particularly ischemic stroke, low eGFR was significantly associated with in-hospital death and at-discharge death/disability. Additionally, high eGFR was found to be associated with at-discharge death/disability.